The Information-Based corporation : - Vincent, David R. (Dow Jones-Irwin, 1990)
This book simplifies the confusing maze of alternatives by offering practical, commonsense solutions. Numerous success stories show you how other companies have used the theories put forth to achieve greater productivity, lower costs, and increase value within their respective companies